Hospitalizations with post-traumatic stress disorder in France between 2013 and 2022: a nationwide retrospective study - Alice Demesmaeker; Florian Dufrenois; Chloé Saint-Dizier; Guillaume Vaiva; Antoine Lamer; Mathilde Horn; Fabien D’Hondt (European Psychiatry)
Abstract